Low-cost solution-processed copper iodide as an alternative to PEDOT:PSS hole transport layer for efficient and stable inverted planar heterojunction perovskite solar cells. Issue 38 (1st September 2015) - Chen, Wei-Yi; Deng, Lin-Long; Dai, Si-Min; Wang, Xin; Tian, Cheng-Bo; Zhan, Xin-Xing; Xie, Su-Yuan; Huang, Rong-Bin; Zheng, Lan-Sun
Abstract : Low-cost solution-processed copper iodide replaces PEDOT:PSS in inverted planar heterojunction perovskite solar cells with high efficiency and enhanced stability. Abstract : Inverted planar heterojunction (PHJ) perovskite solar cells have attracted great attention due to their advantage of low-temperature fabrication on flexible substrates by solution processing with high efficiency. Poly(3, 4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) is the most widely used hole transport layer (HTL) in inverted PHJ perovskite solar cells; however, the acidic and hygroscopic nature of PEDOT:PSS can cause degradation and reduce the device stability. In this work, we demonstrated that low-cost solution-processed hydrophobic copper iodide (CuI) can serve as a HTL to replace PEDOT:PSS in inverted PHJ perovskite solar cells with high performance and enhanced device stability. A power conversion efficiency (PCE) of 13.58% was achieved by employing CuI as the HTL, slightly exceeding the PEDOT:PSS based device with a PCE of 13.28% under the same experimental conditions. Furthermore, the CuI based devices exhibited better air stability than PEDOT:PSS based devices. The results indicate that low-cost solution-processed CuI is a promising alternative to the PEDOT:PSS HTL and could be widely used in inverted PHJ perovskite solar cells.